2011
DOI: 10.1126/science.1210770
|View full text |Cite
|
Sign up to set email alerts
|

Mismatch Repair, But Not Heteroduplex Rejection, Is Temporally Coupled to DNA Replication

Abstract: In eukaryotes, it is unknown if mismatch repair (MMR) is temporally coupled to DNA replication and how strand-specific MMR is directed. Here we fused Saccharomyces cerevisiae MSH6 with cyclins to restrict the availability of the Msh2-Msh6 mismatch recognition complex to either S-phase or G2/M. The Msh6-S cyclin fusion was proficient for suppressing mutations at three loci that replicate at mid-S-phase, whereas the Msh6-G2/M cyclin fusion was defective. However, the Msh6-G2/M cyclin fusion was functional for MM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
115
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 112 publications
(119 citation statements)
references
References 27 publications
(36 reference statements)
4
115
0
Order By: Relevance
“…Finally, the strong enrichment of the mismatch repair proteins MSH2, MSH3, and MSH6 at active elongating forks is consistent with recent data from yeast systems indicating that these proteins travel with the replisome (29). We verified that both MSH2 and MSH6 are associated with the replisome in a pattern mirroring PCNA using conventional immunoblotting (data not shown).…”
Section: ϫ11supporting
confidence: 75%
“…Finally, the strong enrichment of the mismatch repair proteins MSH2, MSH3, and MSH6 at active elongating forks is consistent with recent data from yeast systems indicating that these proteins travel with the replisome (29). We verified that both MSH2 and MSH6 are associated with the replisome in a pattern mirroring PCNA using conventional immunoblotting (data not shown).…”
Section: ϫ11supporting
confidence: 75%
“…We recently showed that MMR is coupled to DNA replication and that the mispair recognition proteins Msh2-Msh6 and Msh2-Msh3 colocalize with the replicative DNA polymerases during DNA replication (55,56). This latter observation led us to investigate whether Pol e might also function in MMR in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…MMR appears to be coupled to the replication fork as evidenced by the timing of MMR and the colocalization of the Msh2-Msh6 mispair recognition complex with replication fork proteins during S phase (55,56). Previous studies suggesting that only Pol δ acts in MMR (50) could be interpreted as implying that the selection of the DNA polymerase used for the gap-filling step of MMR is not directly coupled to DNA replication because Pol δ does not act in leading-strand DNA synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of bacterial MMR have provided a basic mechanistic framework for comparative studies (5). Genetic and cell-biology studies, primarily in Saccharomyces cerevisiae, have identified eukaryotic MMR genes, provided models for how their gene products define MMR pathways, and elucidated some of the details of how MMR pathways interact with replication (1)(2)(3)(4). Reconstitution studies, primarily in human systems, have identified some of the catalytic features of eukaryotic MMR (7-9, 16, 17).…”
mentioning
confidence: 99%
“…DNA replication fidelity | genome instability | mutator phenotype | cancer | mutagenesis D NA mismatch repair (MMR) is a critical DNA repair pathway that is coupled to DNA replication in eukaryotes where it corrects misincorporation errors made during DNA replication (1)(2)(3)(4)(5)(6)(7)(8)(9). This pathway prevents mutations and acts to prevent the development of cancer (10,11).…”
mentioning
confidence: 99%